2017
DOI: 10.1016/j.arth.2016.07.046
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Radiographic Outcomes After Total Hip Arthroplasty Between the Posterior Approach and Direct Anterior Approach With Intraoperative Fluoroscopy

Abstract: Background Radiographic outcomes after total hip arthroplasty (THA) have been linked to clinical outcomes. The direct-anterior approach (DAA) for THA has been criticized by some for providing limited exposure and compromised implant position, but allows for routine use of intra-operative fluoroscopy. We sought to determine whether radiographic measurements differed by THA approach using prospective cohorts. Methods Two reviewers blinded to surgical approach examined 194 radiographs, obtained 4–6 weeks after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 32 publications
(33 reference statements)
3
52
0
1
Order By: Relevance
“…In another radiographic analysis, Lin et al [6] reviewed consecutive cohorts of first posterior approach THAs followed by a series of a similar number of DAA THA patients. Postoperative radiographs were reviewed for acceptability according to established acetabular "safe zone" parameters as well as leg lengths and femoral offset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another radiographic analysis, Lin et al [6] reviewed consecutive cohorts of first posterior approach THAs followed by a series of a similar number of DAA THA patients. Postoperative radiographs were reviewed for acceptability according to established acetabular "safe zone" parameters as well as leg lengths and femoral offset.…”
Section: Discussionmentioning
confidence: 99%
“…The direct anterior approach (DAA) for total hip arthroplasty (THA) has enjoyed a recent increase in popularity [1][2][3]. Proponents note a number of purported benefits of the approach, including a modest early recovery advantage [4], low dislocation rate [5], and favorable radiographic component placement parameters [6]. One of the proposed technical advantages is that this approach is typically performed in the supine position, facilitating easy access to fluoroscopy, which theoretically can minimize errors in component placement and sizing to aid in re-establishing optimal hip biomechanics.…”
Section: Introductionmentioning
confidence: 99%
“…A higher precision and increased accuracy when implanting cup components can lead to a decreased dislocation rate [6,21]. The anterior approach also improves relation of leg length and offset [7].…”
Section: Outcomementioning
confidence: 99%
“…Therefore, the repair of the external rotators and the capsule is of great importance in posterior THA [4]. In addition, the posterior approach is associated with an increased variance of acetabular component positioning [5][6][7]. Poor component positioning increases the risk of dislocation, facilitates increased polyethylene wear, and impingement [5,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the conventional posterior approach (PA) is the most frequently used surgical approach for THA [9] . Some studies show that compared with the PA, the DAA leads to less blood loss, low transfusion rates, shorter surgery times, a shorter length of hospital stay (LOS), low postoperative complication rates and better functional recovery [10][11][12][13][14][15][16][17] . Other studies have shown that DAA is associated with higher postoperative complication rates than is PA [18,19] , especially regarding neuropraxia in the lateral cutaneous nerve of the thigh [18,20] .…”
mentioning
confidence: 99%